Cohesion and its Relationships in the Qur‘ānic text (Theoretical analysis in the light of critical and rhetorical studies) - Faisal, Muhammad (Journal of Islamic and Religious Studies, 2016)
The concept of cohesion is not only a semantics one that exists within the meaning of text; it refers to grammatical relations of the Text The concept of cohesion is not only a semantics one that exists within the meaning of text; it refers to grammatical relations of the Text that exist within surface structure of the text, and that define it as a text. That is why the study of cohesion is important in text linguistics, especially in the Text of holy Qur‘ān. Therefore the ancient researchers have chosen it in different ways in the Qur‘ānic textual analysis. The ancient Arab started the study of Cohesion to prove the Qur‘ānic text as “Mojza” and “ijaaz” because of its organization and arrangement of text according the “Nazem” “Insijaam” “Ittisaaq” “Iltehaam” and many others. The English term that substitutes these terms is just Cohesion and Coherence. So we can say that the Arab was doing well about the discourse/textual analysis of the texts, especially the Qur‘ānic textual cohesion was their main goal. This research work differ from previous works in many aspects, while the researcher focuses on the concept of cohesion and its various aspects, particularly in terms of the cohesion and coherence in Arabic Language in the light of Qur‘ānic text. that exist within surface structure of the text, and that define it as a text. That is why the study of cohesion is important in text linguistics, especially in the Text of holy Qur‘ān. Therefore the ancient researchers have chosen it in different ways in the Qur‘ānic textual analysis. The ancient Arab started the study of Cohesion to prove the Qur‘ānic text as “Mojza” and “ijaaz” because of its organization and arrangement of text according the “Nazem” “Insijaam” “Ittisaaq” “Iltehaam” and many others. The English term that substitutes these terms is just Cohesion and Coherence. So we can say that the Arab was doing well about the discourse/textual analysis of the texts, especially the Qur‘ānic textual cohesion was their main goal. This research work differ from previous works in many aspects, while the researcher focuses on the concept of cohesion and its various aspects, particularly in terms of the cohesion and coherence in Arabic Language in the light of Qur‘ānic text.